American politics and society - McKay, David H. (Wiley-Blackwell, 2018)
"The book is written in a student-friendly style and is supplemented with numerous illustrations and helpful pedagogical features, including chronologies, biographies and definition boxes highlighting key concepts and controversial issues"-- Provided by publisher.